Geography of the Malay Dialect in Kapuas Hulu Regency West Kalimantan - Patriantoro Patriantoro (Journal of English Language Teaching and Linguistics, 2022)
The purposes of this study entitled "Geography of the Malay Language Dialect in Kapuas Hulu Regency, West Kalimantan" are: to describe the lexical variation; to map the lexical variation of Malay dialects; to calculate the differences in the variation of the Malay language; to make a lexical isogloss file in Malay. Three data analysis methods: synchronous comparative method, dialectometric formula to calculate the number of lexical differences in the percentage between observation points, and isogloss file to separate the language variation between observation points in percentage. The research indicated five main findings. First, it produced a description of the variation of the Malay language at 9 observation points. Second, the calculation of lexical differences between observation points in the study area, the lowest difference is at observation points 3 – 4 = 9.5, the highest contrast is at observation points 6 – 7 = 43. Third, the dialectometry calculation results found that language variations in the research area consisted of sub-dialects and speech differences. Fourth, the linguistic distance between observation points is the lowest percentage of 9.5% in area 3 – 4. The linguistic distance between observation points in the highest percentage of 43% was found at observation points 6 – 7. Mapping the lexical variation of Malay found indicated 6 subdialect variations. Fifth, the isogloss line that separates the most language variations through the isogloss file separated the observation points 6 and 7 as many as 43 files. The isogloss file is at least 9.5 files separating observation points 3 and 4.